Emergence of the fourth mobile sulfonamide resistance gene sul4 in clinical Salmonella enterica - Peng, Kai; Deng, Jianping; Zou, Nianli; Sun, Xinran; Huang, Weifeng; Li, Ruichao; Yang, Xiaorong (Frontiers in Microbiology, 2023)
The fourth mobile sulfonamide resistance gene sul4 has been discovered in many metagenomic datasets. However, there is no reports of it in cultured bacteria. In this study, a sul4 positive clinical Salmonella enterica SC2020597 was obtained by conventional Salmonella isolation methods and characterized by species identification and antimicrobial susceptibility testing. Meanwhile, the genomic DNA was sequenced using both long-read and short-read methods. Following that, the complete genome was analyzed by bioinformatics method. The sul4 gene in S. enterica SC2020597 differed from the sul4 identified in metagenomic data by one amino acid and could confer full resistance to sulfamethoxazole. Genetic location analysis showed that the sul4 in SC2020597 was carried by a complex chromosomally integrated hybrid plasmid. ISCR20-like was strongly associated with the mobilization of sul4 by core genetic context analysis. To the best of our knowledge, this is the first report of the emergence of sul4 in clinically cultured S. enterica. More important, the sul4 has the potential to spread to other bacteria with the help of mobile elements.